Frontlijn Namibië - Ya-Otto, John; Peeters, Erika (Leuven: Kritak; Den Haag: Novib; Amsterdam: Komitee Zuidelijk Afrika, 1982)
"John Ya-Otto ; vertaling Erika Peeters Oorspr. titel : Battlefront Namibia"